A coupled stable isotope-size spectrum approach to understanding pelagic food-web dynamics: A case study from the southwest sub-tropical Pacific. (March 2015) - Hunt, B.P.V.; Allain, V.; Menkes, C.; Lorrain, A.; Graham, B.; Rodier, M.; Pagano, M.; Carlotti, F.
Abstract: This study investigated the food web structure of the oligotrophic picophytoplankton-dominated pelagic ecosystem in the vicinity of New Caledonia, within the Archipelagic Deep Basin (ARCH) province of the southwest sub-tropical Pacific. Nitrogen stable isotope (δ 15 N) data were collected for mesozooplankton (0.2–2 mm), macrozooplankton (2–20 mm), micronekton (20–200 mm) and nekton (>200 mm) during 2002–2004 and 2011. Using a coupled δ 15 N size-spectrum approach, we estimated (1) organism trophic level (TL); (2) food chain length (FCL); (3) predator prey mass ratio (PPMR); and (4) transfer efficiency (TE). The role of phytoplankton size structure in determining these parameters was investigated. Applying a trophic enrichment factor (TEF) of 3.4, maximum TL was calculated at 5. The number of TLs spanned by each length class was 1.97 for mesozooplankton, 2.07 for macrozooplankton, 2.75 for micronekton, and 2.21 for nekton. Estimated PPMR was 10, 099:1 for mesozooplankton, 3683:1 for macrozooplankton/micronekton, and 2.44×10 5 :1 for nekton, corresponding to TEs of 6.3%, 8.5% and 2.4%, respectively. PPMR and TE were strongly influenced by the TEF used, and TEF 3.4 likely over and underestimated PPMR and TE, respectively, for mesozooplankton and macrozooplankton/micronekton. Comparatively low PPMR for mesozooplankton and macrozooplankton/micronekton indicated longer food chains and higher connectivity within these groups than for the nekton. Conversely, the high PPMR yet high trophic niche width for the nekton indicated that they prey primarily on macrozooplankton/micronekton, with a relatively high degree of dietary specialisation. Our results are discussed in the context of other marine food webs. The ARCH food chain was found to be 1–1.5 trophic levels longer than the eutrophic micro-/nanophytoplankton-dominated Californian upwelling system, providing empirical support for the role of phytoplankton size in determining FCL. Group specific PPMR estimates demonstrated that it is changes in trophic pathways across the mesozooplankton/macrozooplankton/micronekton groups that are primarily responsible for higher FCL under oligotrophic conditions. Finally, we discuss consistently low δ 15 N values to the east of New Caledonia, and implications for the contribution of diazotroph nitrogen to the pelagic food web in this region.